Three-dimensional electroanatomic mapping characteristics of superior vena cava myocardial sleeve and sinoatrial node in patients with atrial fibrillation - Chen, Xinguang; Lu, Yao; Liu, Yanmin; Chen, Qiushi; Chen, Hongwu; Ju, Weizhu; Yang, Gang; Zhu, Yeqian; Zhao, Pengcheng; Zhang, Jian; Mao, Yangming; Su, Xiaoling; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Three-dimensional activation mapping during sinus rhythm can demonstrate the earliest atrial activation (EAA) site, which could be the sinoatrial node (SAN). We aimed to compare the electroanatomical characteristics of superior vena cava (SVC), myocardial sleeve, and SAN between patients with atrial fibrillation (AF) and non-AF. Materials and methods In this study, 136 patients with AF were assigned to the study group, and 20 patients with premature ventricular contractions (PVCs) who had no history of AF were assigned to the control group. The right atrium (RA) and SVC anatomical activation models were constructed, and the EAA of SAN was delineated using the CARTO3 mapping system. The length of the SVC myocardial sleeve (LSVC) was measured. Results Of the 136 patients, 93 patients had paroxysmal AF (PAF), and 43 patients had persistent AF (PsAF). The LSVC was not significantly different among AF and non-AF, PAF, and PsAF. The LSVC in men was longer than in women (42.1 ± 9.4 mm vs. 35.4 ± 8.1 mm, p < 0.001). The LSVC was longer in patients with EAA of SAN above the RA-SVC junction than in those with below the RA-SVC junction (p < 0.001). The EAA of SAN was below the RA-SVC junction in 64/136 (47.1%) and was above the junction in 72/136 (52.9%) patients with AF. The spatial distribution of the EAA of SAN between PAF and PsAF was not different. There was a trend of statistical difference in the distribution of the EAA of SAN between PsAF and non-AF. Conclusion The EAA of SAN was located in the SVC in most of the patients, especially in patients with PsAF.